Analysis Impact Application SFAS 72 On Financial Performance - Irfani, Cahaya Fajrina Putri; Efrianti, Desi; Evianti, Dessy; Amrulloh, Amrulloh; Setiawan, Hendra (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The property, real estate and building construction sectors play an important role in the economy and development in Indonesia. The property, real estate and building construction sectors are currently facing budget problems. This is caused by limited APBN funds, which hinder the achievement of development goals. Real Estate refers to assets that include land, buildings, and other fixed resources, which include ownership rights to property. Meanwhile, building construction refers to the construction of facilities and infrastructure in a certain area, such as the construction of buildings, roads, etc. This research is included in the mixed type of research because it uses quantitative and qualitative methods. The data used comes from officially registered sources, namely the financial reports of Property Companies listed on the Indonesia Stock Exchange in 2018 and 2021. The object of this research is financial performance variables. The research subject is what and who is used as the research unit. In this research, the research subjects are property companies listed on the Indonesia Stock Exchange in 2018 and 2021. The research results refer to the output of the paired samples test table shows that the Sig. (2-tailed) there is no difference before and after the implementation of the PSAK. Referring to the output of the test statistics table, it is known that the value of Asymp.Sig. (2-tailed) 0.117 which is 0.05. Thus, at a real level of 5% it can be concluded that the implementation of PSAK 72 (currently PSAK 115) does not provide significant changes to the financial statements. Keywords: Property and PSAK 72 (now PSAK 115)